IMPACT OF URBANIZATION IN EKAMRA KSHETRA, ODISHA: PARAMETRIC ANALYSIS OF VARIATIONS - Mukherjee, Gayatri; Roy, Madhumita; Dutta, Sourovee (International Journal of Research -GRANTHAALAYAH, 2025)
Urbanization is a complex mechanism of development of spaces which have adversely affected the historic towns in India. Ekamra Kshetra, Bhubaneswar is one such historic settlement dating back to the 12th century CE. The settlement has been dotted with several temples built across the 12th to 18th century by the various dynasties who ruled Odisha and Ekamra Kshetra was considered as a pious religious centre with the settlements developed around the temples. With the transformation of Bhubaneswar into a modern planned city of independent India, in 1948, the original planned city was planned earmarking the historic part as a separate entity with minimal effect of urban sprawl. However, with the advent of industries and population explosion in Bhubaneswar, especially after the 1980s, the historic part of the city has been at the receiving end of rapid urban sprawl, with massive modern constructions which have severely affected the original spatial nature and eventually the historic fabric of the Ekamra Kshetra has been lost. This paper attempts to undertake an analysis of these change in the historic fabric through definition of various parameters following a detailed visual survey of a selected area in Ekamra Kshetra. Based on the findings, a regression and ordinal analysis was undertaken to understand the calculate the likelihood of change in the original fabric of the historic town.